Demokrat Parti Dönemi’nde haftalık muhalif bir dergi: Çakmak (1956-1957) - Caymaz, Cabir (My University, 2024)
Bu çalışmanın konusunu Demokrat Parti iktidarının basın ve muhalif siyaset üzerinde baskısının yoğun şekilde hissedildiği 1957 genel seçimlerine doğru giden süreçte çıkan ve Türk siyasetinde muhalif tarzda siyasi bir mecmua olan Çakmak dergisi oluşturmaktadır. İlk sayısı Mart 1956’da çıkan ve haftalık bir dergi olan Çakmak dergisinin 50 sayı sonunda 1957 Şubat ayında yayın hayatı sona ermiştir. Türkiye Köylü Partisi’nin genel başkanı ve aynı zamanda yayıncı olan Tahsin Demiray’ın çıkarttığı bu dergi, Demokrat Parti iktidarına muhalif olmakla birlikte Cumhuriyet Halk Partisi’ni muhalefet olarak görmemiş; siyasette çoğulculuğu öne sürmüştür. Dergiyi çıkaranlar derginin ismini belirlerken Fevzi Çakmak’ın soyadından esinlenmiş; milliyetçi, muhafazakâr ve liberal özelliklere sahip siyasi anlayış gütmüş ve Demokrat Parti’ye muhalefeti başta olmak üzere dönemin iç ve dış siyasi olaylarına bu anlayışla bakmıştır. Bu çalışmada Çakmak dergisinin fikirleri, iç ve dış siyasete bakışındaki özellikleri ile muhalif siyasi pozisyondaki yeri ortaya koyulmaya çalışılmıştır.

The subject-matter of this study is the Çakmak magazine, which was published as an opposition-style political magazine in Turkish politics during the period leading up to the 1957 general elections, when the pressure of the Democrat Party government on the press and opposition politics was intensely felt. The Çakmak weekly began to be published in March 1956; after a period of 50 issues between March 1956 and February 1957, it ended its publications. This magazine, published by Tahsin Demiray, the Chairman of the Turkish Peasants' Party and also a publisher, was an opponent of the Democrat Party government, but did not see the Republican People's Party as an opposition force and emphasized pluralism in politics. It was the surname of Fevzi Çakmak that gave the weekly its title; it followed a political approach which has the characteristics of nationalism, conservativism and liberalism, and viewed the domestic and foreign political events of the period, especially the opposition to the Democrat Party, from this perspective. This study attempts to reveal the Çakmak’s magazine views, how it regarded domestic and foreign policies and how it positioned itself as an oppositional force.
Keywords: basın; Çakmak dergisi; Çakmak magazine; Democrat Party period; Demokrat Parti dönemi; muhalefet; opposition; Periodicals; political magazine; Political parties; press; siyasi mecmua; Siyasi partiler; Süreli yayınlar; Turkey; Türkiye